Types of Knowledge Involved in a Stamp Duty Valuation Process - Ab Latif, Siti Nur Farhana; Rosman, Siti Hasniza; Nawawi, Abdul Hadi; Abdullah, Mohamad Isa (2018)
Generally, there are different kinds of knowledge that exist in stamp duty valuation which is sometimes taken for granted by some of the personnel involved. These knowledge contains useful information for the future. There are also people who do not know that they are an experts on a particular types of knowledge. This paper will explore the types of knowledge involved in stamp duty valuation process.